CHARACTERISTICS OF SOLAR STILL WITH HEAT EXCHANGERS ON THE COVER GLASS - Nanda, Ignasius Dinang Yudra; Sambada, F. A. Rusdi; Yulianto, Yulianto; Sitio, Angelina Boru (International Journal of Applied Sciences and Smart Technologies, 2020)
Drinking water is one of the main needs of human life. Water sources do not always have the feasibility to drink. Distillation is one way to obtain potable water. Distillation can influence on drinking water quality. Low performance is a major problem in distillation. One way to improve performance is by increasing the input water temperature. One way to increase the input water temperature by utilizing heat energy on the cover glass. This study aims to improve the performance of solar energy water distillation and input water temperature by a heat exchanger. This research method is experimental. The measured variables are absorber temperature in the distillation model (T1), glass temperature (T2), ambient temperature (Ta), amount of distilled water produced (m) and heat energy coming from solar energy (G). This research uses variations, namely with a white or black heat exchanger and without heat exchanger. Water quality tested using 4 parameters such as microbiology, inorganic chemistry, physical and chemical. Based on this study, the best results produced by a black heat exchanger using a water flow rate of 2 l/h which produce distillation water 422 ml (480 ml/(m2.h)) and efficiency value of 79.74%. While the best results using white heat exchanger is using 0.7 l / hour water flow rate which produces distillation water of 497 ml/(m2.h) and efficiency value of 82.63%, Distilled water has increased in quality even though it has not met the standards No. 492 of 2010Keywords: distillation, solar energy, glass cover, water quality, efficiency